2019
DOI: 10.3390/catal9050401
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression, and Characterization of a Novel Thermostable and Alkaline-stable Esterase from Stenotrophomonas maltophilia OUC_Est10 Catalytically Active in Organic Solvents

Abstract: A thermostable and alkaline-stable novel esterase (Est7) was identified through the whole genome sequencing of Stenotrophomonas maltophilia OUC_Est10. The open reading frame of this gene encoded 617 amino acid residues. After heterologous expression in Escherichia coli BL21 (DE3), the purified Est7 was separated as a single protein and presented a molecular mass of 70.6 kDa. Multiple sequence alignment indicated that Est7 had a typical catalytic triad (Ser-Asp-His) and the conserved sequence (GDSL) typical of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…Sodium dodecyl sulphate (SDS), an anionic surfactant, which can destroy the non-covalent bonds between enzyme molecules and change the conformation of enzyme also, inhibited FAE activity significantly in a concentration dependent manner (Table 3). Inhibition of enzyme activity by SDS is in accordance with the observed negative impact of this compound on esterase from Stenotrophomonas maltophilia (Gao et al, 2019). Ascorbic acid also showed detrimental effect on the purified pearl millet esterase (Table 3).…”
Section: Effect Of Modulators: Data Presented Insupporting
confidence: 80%
“…Sodium dodecyl sulphate (SDS), an anionic surfactant, which can destroy the non-covalent bonds between enzyme molecules and change the conformation of enzyme also, inhibited FAE activity significantly in a concentration dependent manner (Table 3). Inhibition of enzyme activity by SDS is in accordance with the observed negative impact of this compound on esterase from Stenotrophomonas maltophilia (Gao et al, 2019). Ascorbic acid also showed detrimental effect on the purified pearl millet esterase (Table 3).…”
Section: Effect Of Modulators: Data Presented Insupporting
confidence: 80%
“…The complete protein sequence of PTCL1-EstA was submitted to the webserver, and the homologous protein structure of PTCL1-EstA (QMEAN value: −1.30) constructed by the program was evaluated using the evaluation statistics available on the website. The most pronounced homology was obtained for esterase A from Arthrobacter nitroguajacolicus Rü61a [30] (PDB ID: 3zyt.1; GMQE value: 0.82), esterase A from Caulobacter crescentus [31] (PDB ID: 5gkv.1; GMQE value: 0.68) and betalactamase from Chromobacterium violaceum [32] (PDB ID: 5evl.1; GMQE value: 0.63). Both esterase A and PTCL1-EstA are from the genus Arthrobacter, with >98% protein sequence similarity.…”
Section: Enzymatic Properties Of Ptcl1-estamentioning
confidence: 99%
“…Genomic DNA of P. aurescens TC1 was prepared by the reported method [31][32][33]. The primers PTCL1-EstA For and PTCL1-EstA Rev were designed based on the putative AAAA_RS19005 gene (NCBI gene ID: 29622418) of P. aurescens TC1 (AABI_ classification ID: 290340) to obtain the gene fragment PTCL1-EstA.…”
Section: Gene Cloning and Expression Vector Constructionmentioning
confidence: 99%
“…Thus, TM1022 has a better pH stability. After incubation at 90 °C for 8 h, TM1022 retained 57% of its enzymatic activity, showing higher thermal stability than other thermophilic carboxylesterases. The potent inhibition of PMSF suggests that serine residues are potentially associated with the catalytic site of TM1022, consistent with the predicted catalytic triad (Ser-Asp-His). Experiments on the effects of surfactants and organic solvents showed that TM1022 is very stable when exposed to chemical reagents.…”
Section: Discussionmentioning
confidence: 72%